Classroom Learning Activities and Reading Comprehension of Junior High School Students - Elizabeth Meiske Maythy Lasut; Meily Ivane Esther Neman (Indonesian Journal of Education and Social Studies, 2025)
This quantitative study aimed to determine the relationship between classroom learning activities and reading comprehension of the students who were registered at a secondary school.  This study utilized the descriptive correlational research design.  A self-constructed instrument was used for this study and convenience sampling method was applied in gathering the data. Respondents were asked to rate each statement for classroom learning activities inventory by using a five-point Likert scale. Frequency, percentage, and mean were used to determine the level of each variable.  Meanwhile, to find out the relationship between variables, Pearson Product Moment was utilized.  It was found out that the extent of classroom learning activities (M =3.93) experienced by the students was on ‘high’ level, and student’s reading comprehension (M = 82.25) was on ‘high’ level as well.  Moreover, the results showed that significant relationships occurred between classroom learning activities (r = .946, p = .00 < α = 0,05) and student’s reading comprehension.  In conclusion, students’ reading comprehension significantly related to what classroom learning activities they experienced.